Whole Genome Sequence Comparisons and “Full-Length” cDNA Sequences: A Combined Approach to Evaluate and Improve Arabidopsis Genome Annotation - Castelli, Vanina; Aury, Jean-Marc; Jaillon, Olivier; Wincker, Patrick; Clepet, Christian; Menard, Manuella; Cruaud, Corinne; Quétier, Francis; Scarpelli, Claude; Schächter, Vincent; Temple, Gary; Caboche, Michel; et al.

(untitled) (Genome Research, 2004)
To evaluate the existing annotation of the Arabidopsis genome further, we generated a collection of evolutionary conserved regions (ecores) between Arabidopsis and rice. The ecore analysis provides evidence that the gene catalog of Arabidopsis is not yet complete, and that a number of these annotations require re-examination. To improve the Arabidopsis genome annotation further, we used a novel “full-length” enriched cDNA collection prepared from several tissues. An additional 1931 genes were covered by new “full-length” cDNA sequences, raising the number of annotated genes with a corresponding “full-length” cDNA sequence to about 14,000. Detailed comparisons between these “full-length” cDNA sequences and annotated genes show that this resource is very helpful in determining the correct structure of genes, in particular, those not yet supported by “full-length” cDNAs. In addition, a total of 326 genomic regions not included previously in the Arabidopsis genome annotation were detected by this cDNA resource, providing clues for new gene discovery. Because, as expected, the two data sets only partially overlap, their combination produces very useful information for improving the Arabidopsis genome annotation.